On Metaphysical Guilt and Infinite Responsibility: K. Jaspers and E. Levinas. - Saldukaitytė, Jolanta (Problems / Problemos)
This paper discusses guilt and responsibility in Jaspers and Levinas. First, it explores the concept of guilt in Jaspers and shows that while “metaphysical guilt” deepens the existential dimension of human life it remains indifferent to the moral dimension of guilt and responsibility uncovered by Levinas. Second, the paper explores the notions of guiltless responsibility and unavoidable guilt in Levinas and shows that responsibility is not limited to specific wrongdoing or explicit acknowledgment of guilt. By drawing out these differences between Jaspers and Levinas, the author asks if Levinas’s approach might provide illuminating guidance to talk about our guilt and responsibility for the Holocaust as well as other social events.